Character Education in Forming a Pancasila Student Profile in Junior High School Students - Ningsih, Tutuk; Suwandi; Rohmat; Rahman, Riki (Advances in Humanities and Contemporary Studies, 2024)
This research aims to understand the importance of character education in forming the profile of Pancasila students. The Pancasila student profile is a new breakthrough in the education curriculum in Indonesia and is also intended as something oriented towards increasing the character values of students as the next generation of the Indonesian nation. This research uses a qualitative approach to obtain relevant data and data sources. The subjects in this research are the characters currently depicted in the students. Character as part of a person’s behavior and interpreted as a form of moral actualization is an ideal indicator of achieving educational goals. Good behavior will indicate good character. Character that is well built from an early age will have an influence in adulthood. A person’s character cannot be changed instantly. The result is that the initial foundation that was built was on a spiritual basis. In reality, moral decadence is currently very worrying. The character of many junior high school (SMP) students is far from character values, let alone Pancasila values. Through character education, it is hoped that we will be able to solve problems related to moral decline. Through character education, it is also hoped that it can shape the profile of Pancasila students. Middle school students who are currently experiencing a change in identity must receive more character awareness.